Penggunaan Teknologi Dalam Dakwah Dan Penyebaran Islam - Sari Aryani; Sheli Sellviana; Khoirun Nisa; Sigit Gimnastiar; Dwi Noviani (Journal of Innovative and Creativity, 2025)
This research examines the transformation of Islamic da'wah through the utilization of digital technology in Indonesia as the country with the largest Muslim population in the world. Using a qualitative approach and case study method, this study analyzes how social media platforms (Instagram, YouTube, TikTok, Facebook, WhatsApp), digital religious applications (Muslim Pro, Al-Quran Indonesia, MyQuran), and Islamic fintech have revolutionized the methods of spreading Islamic teachings that were previously limited to conventional approaches. The research findings indicate that digital technology has exponentially increased the reach of da'wah, democratized access to Islamic education, and facilitated more transparent and efficient ZISWAF (zakat, infaq, sadaqah, waqf) transactions. However, digital da'wah also faces serious challenges such as the spread of religious hoaxes, the emergence of informal authorities, online radicalization, and commodification of piety. This research recommends strategies for optimizing digital da'wah through increasing digital literacy among preachers, collaboration between ulama and technology practitioners, verification of religious content, and development of regulations that support da'wah innovation while maintaining the authenticity of Islamic teachings.